Tindak Pidana Penipuan dalam Perspektif Pasal 386 KUHP dan Hadits Riwayat Ahmad - Hilmi, Muhammad; Arifin, Tajul (Indo Publishing, 2025)
This research is motivated by the fact that Article 386 of the Criminal Code states that